PENGGUNAAN MEDIA MOVIE MAKER DALAM KETERAMPILAN BERBICARA BAHASA ARAB PADA SISWA KELAS V A MIN BAWU JEPARA - Naili Vidya Yulistyana; Zukhaira Zukhaira; Retno Purnama Irawati (Universitas Negeri Semarang, 2022)
The reason why the researcher hold the research in class VA MIN Bawu Jepara is the limitation of the learning media used to improve students Arabic speaking skill in that class. This research uses the action research type which done in 2 cycles. The research instrument for collecting the data, technique for collecting the data, and data analysis use test and non test. The research result is gotten from the average score in the first meeting which is 68,97 and second meeting is 72,75, so it is gotten the average from the cycle I 70, 86. While the everage score in the first meeting from the second cycle is 85,75 and the second meeting is 91,5, so it is gotten the average score from the second cycle which is 88,62. So, it shows the improvement start from cycle I to the cycle II which is 25, 06 %. The data analysis result from non test based on the result also shows that there is the positive attitude alteration towards the students in V A MIN Bawu Jepara.